ChemInform Abstract: Facile Installation of 2‐Reverse Prenyl Functionality into Indoles by a Tandem N‐Alkylation—Aza‐Cope Rearrangement Reaction and Its Application in Synthesis. Issue 22 (12th May 2016) - Chen, Xiaobei; Fan, Huaqiang; Zhang, Shilei; Yu, Chenguang; Wang, Wei
Abstract: The N‐alkylation of enamine (II) with bromides (I) and (IV) followed by a microwave‐assisted aza‐Cope rearrangement/hydrolysis cascade reaction gives rise to aldehydes (III) and (V).